MULTIMODAL ANALYSIS OF RIAU ARCHIPELAGO PROMOTION VIDEO - Dewi Nurmala (PHILOLOGY Journal of English Language and Literature, 2022)
Multimodal is the study of discourse analysis relates to the systemic functional semiotics. Multimodal as the place of visual communication in a given society can only be understood in the context of the range of the forms or modes of public communication. such as gesture, speech, image, writing, 3D objects, color, music and the others.In visual grammar, the three metafunctions are renamed as representational, interactive, and compositional.The objective of the study is to find out the representational meaning in a visual element of Riau Archipelago Video Promotion. The data used is the visual element of the video. The method used is qualitative research. The result of the study is the conceptual representation displayed in the video is categorized into the classificational process, analytical process and symbolic process. Then,the narrative representation mainly belongs to action processes and reactional processes.